Fatigue tests and design of CFRP-strengthened CHS gap K-joints. (June 2021) - Tong, Lewei; Xu, Guowen; Zhao, Xiao-Ling; Yan, Yang
Abstract: This paper presents an experimental study on the fatigue behaviour of circular hollow section (CHS) gap K-joints strengthened by carbon fibre-reinforced polymer (CFRP) sheets (CFRP-CHS K-joint). Eight CFRP-CHS K-joints and three reference un-strengthened CHS gap K-joints were tested under cyclic axial loading. Fatigue failure modes of the CFRP-strengthened and un-strengthened joints were determined and compared. Fatigue lives in three fatigue failure criteria were recorded: crack-initiation fatigue N 2, through-thickness fatigue N 3, and end-of-test fatigue N 4 . The comparisons indicate that CFRP-CHS K-joints have a longer fatigue life than un-strengthened joints in the same nominal stress range, regardless of fatigue failure criteria ( N 2, N 3, or N 4 ). The increase in N 3 was approximately 138%, on average. No significant difference in fatigue data in terms of hot spot stress range was found between the CFRP-strengthened and un-strengthened joints. Based on the experimental fatigue data, a modified S r, h s - N curve based on the CIDECT recommended curve was proposed for CFRP-CHS K-joints. Highlights: Fatigue tests were conducted on CFRP-strengthened and un-strengthened CHS gap K-joints. Failure modes and fatigue life of CFRP-CHS K-joints are reported and discussed. CFRP strengthening significantly increases the fatigue life of CHS gap K-joints. A modified S r, h s - N curve is proposed for CFRP-CHS K-joints.